Blood pressure and cognitive performances in middle-aged adults: the Aging, Health and Work longitudinal study. Issue 6 (June 2019) - Rouch, Laure; Cestac, Philippe; Hanon, Olivier; Ruidavets, Jean-Bernard; Ehlinger, Virginie; Gentil, Catherine; Cool, Charlène; Helmer, Catherine; Dartigues, Jean-François; Bouhanick, Béatrice; Chamontin, Bernard; Sallerin, Brigitte; et al.
Abstract : Background: Our objective was to investigate the impact of both prevalent and incident hypertension on cognition in middle-aged individuals followed up for 10 years and to explore the extent to which blood pressure control by antihypertensive drugs could modify this relationship. Method: Three thousand, two hundred and one participants from the Vieillissement Santé Travail (Aging, Health and Work) (VISAT) cohort study, aged 32, 42, 52 and 62 years at baseline were followed up 5 and 10 years later. Blood pressure, antihypertensive medication use as well as memory and speed cognitive performances were assessed at baseline and follow-up. Linear mixed models were used for analyses. Results: At 10-year follow-up, compared with nonhypertensive participants, prevalent hypertensive individuals showed poorer global cognitive performances ( β = −2.99 ± 0.96, P = 0.002 for participants aged 32 or 42 years at baseline and β = −5.94 ± 1.00, P < 0.001 for those aged 52 or 62). Patients with incident hypertension had poorer global cognitive performances over time compared with patients without hypertension. When considering prevalent hypertension and blood pressure control status by antihypertensive therapy, untreated and uncontrolled hypertension were associated with poorer cognitive performances than controlled and no hypertension (untreated hypertension compared with no hypertension: β = −5.51 ± 0.75, P < 0.001; uncontrolled hypertension compared with no hypertension: β = −6.13 ± 1.40, P < 0.001). Conclusion: Our findings showed that both prevalent and incident hypertension are associated with poorer global cognitive function in middle-aged individuals and suggested a potential preventive effect of antihypertensive therapy on cognition. Thus, for brain functioning, heightened efforts to detect hypertension and adequately treat it are of critical importance. Abstract : Supplemental Digital Content is available in the text